Back to the roots: defining the core microbiome of Sorghum bicolor in agricultural field soils from the centre of origin. Issue 12 (24th November 2022) - Abera, Sewunet; Shimels, Mahdere; Tessema, Taye; Raaijmakers, Jos M; Dini-Andreote, Francisco
Abstract: Sorghum is a major staple crop in sub-Saharan Africa with yields severely impacted by biotic and abiotic factors. Here, we analysed the taxonomic diversity and biogeographical distribution of bacterial taxa of 48 agricultural fields along a transect of approximately 2000 km across the Ethiopian sorghum belt, the centre of origin of sorghum. The ultimate goal is to identify—yet-unexplored—beneficial plant–microbe associations. Based on bulk soil bacterial communities and DArT-SNP analyses of 59 sorghum accessions, we selected three microbiologically distinct field soils and 12 sorghum genotypes, including commercial varieties, wild relatives, and farmer-preferred landraces. The results showed a core rhizosphere microbiome of 2125 amplicon sequence variants (ASVs), belonging to eight bacterial families consistently found across the three soil types and the 12 sorghum genotypes. Integration of the rhizosphere bacterial community analysis with DArT-SNP sorghum genotyping revealed the association of differentially abundant ASVs with sorghum genotypic traits, including the distinct recruitment of Pseudomonadaceae by the stay-green, drought-tolerant, and wild sorghum genotypes. Collectively, these results provide new insights into the core and accessory bacterial taxa in the sorghum rhizosphere in the centre of origin, setting a baseline for targeted isolation and functional characterization of putative beneficial rhizobacteria. Abstract : This study characterizes the core rhizobacterial microbiota of diverse sorghum genotypes grown in field soils collected from the centre of origin in Ethiopia.